Multi-center, prospective, non-interventional, observational study on the efficacy and safety of Mirabek® in adult patients with overactive bladder - Jee Soo Park; Won Sik Jang; Jongchan Kim; Moon-Hwa Park; Won Sik Ham (Investigative and Clinical Urology)
"Purpose: Mirabegron, the first-in-class beta-3 agonist, is the mainstay medication for overactive bladder (OAB). The aim of this study was to investigate the efficacy and safety of generic drugs of mirabegron (Mirabek®) in adults diagnosed with OAB through a multicenter, prospective, non-interventional observational study. Materials and Methods: Adult patients with OAB prescribed Mirabek® SR Tab. 50 mg for the first time were recruited from hospitals between September 2021 and September 2022. Participants underwent baseline registration followed by two follow-ups at 4- and 8-week intervals. Data on demographics, medical history, OAB symptoms, vital signs, medication administration, and adverse events were collected. Results: Among 1,714 patients, Mirabek® SR Tab. 50 mg effectively improved OAB symptoms over an 8-week treatment period, with significant differences in symptom improvement between baseline and both 4- and 8-week time points as well as between 4 weeks and 8 weeks. The incidence rate of adverse events was 0.70%; most cases were mild with no severe reactions. Conclusions: This study demonstrated that Mirabek®, a generic drug of betmiga, is an effective and safe treatment option for adults with OAB. Furthermore, the introduction of generic drug reduced the costs of prescription drugs and expanded the opportunity for many patients to access mirabegron."